1986
DOI: 10.1038/ki.1986.82
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration surface in type I diabetes mellitus

Abstract: Previously we have shown that relative glomerular mesangial expansion was an important correlate of renal dysfunction in diabetes. To extend the understanding of structural functional relationships, 37 patients with type I diabetes mellitus for 5 to 33 years were studied with multiple creatinine clearance (Ccr), urinary albumin excretion, and blood pressure measurements, and percutaneous renal biopsies. Glomerular volume and percent sclerosed glomeruli were determined; quantitative stereology was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
107
4

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(122 citation statements)
references
References 19 publications
11
107
4
Order By: Relevance
“…Diabetic subjects who subsequently develop nephropathy have severe mesangial expansion with a progressive decline in glomerular filtration rate as the filtration surface area is gradually reduced [39]. It is uncertain whether the membrane transport defect we have described is a marker for the tendency for mesangial expansion to occur, for only 30% of Type 1 diabetic patients develop nephropathy.…”
Section: Discussionmentioning
confidence: 90%
“…Diabetic subjects who subsequently develop nephropathy have severe mesangial expansion with a progressive decline in glomerular filtration rate as the filtration surface area is gradually reduced [39]. It is uncertain whether the membrane transport defect we have described is a marker for the tendency for mesangial expansion to occur, for only 30% of Type 1 diabetic patients develop nephropathy.…”
Section: Discussionmentioning
confidence: 90%
“…Regardless of the mechanism(s), the structural changes associated with JGA T-cell infiltration could be protective of the glomerulus. Ultimately, loss of filtration surface as a consequence of mesangial expansion is an important mechanism of GFR loss in diabetic nephropathy [30]. Thus, the increased filtration surface in JGA T-cell positive patients could provide a greater safety margin as mesangial expansion occurs [30].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, loss of filtration surface as a consequence of mesangial expansion is an important mechanism of GFR loss in diabetic nephropathy [30]. Thus, the increased filtration surface in JGA T-cell positive patients could provide a greater safety margin as mesangial expansion occurs [30]. It is possible that this is reflected in the higher AER in the T-cell negative group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not believe this explains the contrasting results. The Minneapolis Group have shown that there is no difference in MGV in normotensive compared with hypertensive type 1 patients [29] and Table 3 (S. M. Mauer, unpublished data). Thus, it is possible that some factor other than blood pressure influences the increase in MGV in the type 2 diabetic patients.…”
Section: Are the Differences Due To Blood Pressure?mentioning
confidence: 96%